Unrevealed sources of revenue – Disclosure and taxation procedures in Poland - Hybka, Małgorzta Magdalena (Publishing House of the Wrocław University of Economics, 2009)
The article gives an overview of the taxation procedures applied in Poland to the afore-mentioned income. It focuses on two main issues. First, it presents the methods of personal income fraud detection – tax and fiscal inspections as well as information collection measures. Secondly, it describes proceedings concerning the assessment of tax on the income in question. Moreover, the author evaluates the effectiveness of the activities undertaken in this regard by tax offices and fiscal inspection offices on the basis of the data published by the Supreme Chamber of Control in Poland.(fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 207-216